2004
DOI: 10.1097/01.ccm.0000120051.79520.b6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inflammatory response and sequestration of blood iron transferrin complexes in a rat model of lung injury resulting from exposure to low-frequency shock waves

Abstract: The observed dynamics in polymorphonuclear leukocyte alterations in peripheral blood after OPW exposure were similar to those found recently in clinical observations of nonpenetrating injury and in animal models of infectious insults. Therefore, our data suggest that the main pattern of proinflammatory alterations in the rat model of lung injury induced by exposure to long-duration shock wave is similar to patterns that are characteristic of major trauma. The data further suggest that the expression of polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…We saw significant increases in neutrophils in the blood across all time points, which may in part be driven by circulating chemokines and complement products previously reported to be elevated in PBLI 12,19,36,37 . Additionally, we observed a rapid increase in neutrophils in the lung at 1 and 3hr, returning to baseline by 6hr.…”
Section: Neutrophilsmentioning
confidence: 88%
See 3 more Smart Citations
“…We saw significant increases in neutrophils in the blood across all time points, which may in part be driven by circulating chemokines and complement products previously reported to be elevated in PBLI 12,19,36,37 . Additionally, we observed a rapid increase in neutrophils in the lung at 1 and 3hr, returning to baseline by 6hr.…”
Section: Neutrophilsmentioning
confidence: 88%
“…PBLI causes damage to lung tissue that promotes cellular infiltration, through the destructive effects of stress and shear waves at air-fluid tissue boundaries. In PBLI, studies have shown neutrophil infiltration histologically or by assaying activation markers such as MPO in BALF or lung homogenates [9][10][11][12]14,18,19,34 . Our histological data showed marked cellular infiltration and free erythrocytes due to alveolar haemorrhage consistent with previous human and rodent reports 11,35 .…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that both these factors acting together or alone can generate highfrequency stress waves and lower-frequency shear waves, and both types are potentially injurious to the tissue. 13,41 Experimental evidence collected in the past suggests that blastrelated injury is governed by three key input parameters associated with the shockwave: (1) peak overpressure, (2) the overpressure (positive phase) duration, and (3) positive phase impulse (the integral of overpressure in the time domain). To evaluate the effect of blast exposure, various animal models were exposed to different forms of blast ranging from direct exposure to live explosives and controlled blast waves.…”
Section: Discussionmentioning
confidence: 99%